The deterrence effect of immigration enforcement in transit countries: Evidence from Central American deportees - Fernanda Martínez Flores (RWI - Leibniz-Institut für Wirtschaftsforschung, 2018)
Immigration enforcement cooperation between final destination and transit countries has increased in the last decades. However, the question whether these measures are successful in deterring undocumented migrants has not been previously explored by the empirical literature. This paper examines whether the Southern Border Plan, an immigration enforcement program implemented by the Mexican government in 2014, has curbed intentions of unauthorized migrants from El Salvador, Guatemala, and Honduras to migrate to the United States. Combining surveys from Central American and Mexican deportees and using a DiD approach, I find that increased enforcement in Mexico decreases the likelihood of attempting repeated unauthorized crossings. The results indicate that in the short-run the cooperation between destination and transit countries could be effective in deterring undocumented migrants. – – Zur Verbesserung der Zuwanderungskontrolle gab es in den vergangenen Jahren vermehrt Kooperationen zwischen Zielländern von Einwanderern und Transitstaaten. Die Frage, ob diese Maßnahmen nicht dokumentierte Migration erfolgreich reduzieren konnten, wurde bisher jedoch nicht empirisch analysiert. Die vorliegende Studie untersucht, ob der Southern Border Plan, ein durch die mexikanische Regierung im Jahr 2014 eigeführtes Programm zur Zuwanderungskontrolle, die Absichten von irregulären Migrantinnen und Migranten aus El Salvador, Guatemala und Honduras in Mexiko, in die Vereinigten Staaten weiterzureisen, reduziert hat. Mithilfe von Daten von mittelamerikanischen und mexikanischen abgeschobenen Migrantinnen und Migranten und unter Verwendung eines Differenzen-von-Differenzen-Ansatzes finde ich, dass eine erhöhte Kontrolle die Wahrscheinlichkeit eines erneuten versuchten irregulären Grenzübertritts der Migrantinnen und Migranten reduziert. Vor diesem Hintergrund scheint die Kooperation bei der Zuwanderungskontrolle zwischen Transit- und Zielland zumindest kurzfristig effektiv zu sein.
Keywords: F22; K42; K37; O15; 330; immigration enforcement; deportees; Central American migrants; unauthorized; undocumented; remigration; transit countries